2023
DOI: 10.1039/d2ce01632j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of non-covalent interactions on the coordination geometry of Ni(ii) in Ni(ii)–M(ii) complexes (M = Zn and Hg) with a salen-type N2O2 Schiff base ligand and thiocyanate ion as the coligand

Abstract: A nickel(II)-zinc(II) complex, [(NiL)Zn(µ1,3-NCS)2]n (1) and a nickel(II)-mercury(II) complex, [{(NiL)Hg(µ1,3-SCN)(SCN)}2] (2) (where H2L = N,N'-bis(salicylidene)-1,3-propanediamine) have been synthesized via metalloligand approach of which former is a 2D coordination polymer but...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
1
0
0
Order By: Relevance
“…The complexes behave as monomers in solution at 23 °C, as indicated by the solution state Evans method magnetic moment measurements, and 19 F NMR in CD 3 CN shows that the triflate anion dissociates in solution (see SI). The vanadium­(V/IV) redox event for V-Na, V-K, and V-Ba is reversible and shifts anodically with an increase in the cation charge, consistent with the effect on other heterobimetallic complexes in this ligand framework. , , Computational studies were also performed, and the same trend is observed, though the simple model used in the calculations overestimates the increase in E 1/2 as the cation charge increases (see SI for computational details and Table S3 for values). The vanadium­(V/IV) reduction potential for the monocations (V-Na and V-K) shifts 90–130 mV more positive than (salen)­V­(O) and 114–164 mV more positive than (salen-OMe)­V­(O).…”
Section: Resultssupporting
confidence: 56%
“…The complexes behave as monomers in solution at 23 °C, as indicated by the solution state Evans method magnetic moment measurements, and 19 F NMR in CD 3 CN shows that the triflate anion dissociates in solution (see SI). The vanadium­(V/IV) redox event for V-Na, V-K, and V-Ba is reversible and shifts anodically with an increase in the cation charge, consistent with the effect on other heterobimetallic complexes in this ligand framework. , , Computational studies were also performed, and the same trend is observed, though the simple model used in the calculations overestimates the increase in E 1/2 as the cation charge increases (see SI for computational details and Table S3 for values). The vanadium­(V/IV) reduction potential for the monocations (V-Na and V-K) shifts 90–130 mV more positive than (salen)­V­(O) and 114–164 mV more positive than (salen-OMe)­V­(O).…”
Section: Resultssupporting
confidence: 56%
“…The zones with relatively lower electron density will usually have "positive" or at least "less negative" electrostatic potential. Similar noncovalent interactions are also present in the complexes of other transition and nontransition metals, e.g., aerogen or noble gas bonding (NgB, group 18), 10 pnictogen bonding (PnB, group 15), 11 tetrel bonding (TtB, group 14), 12 triel bonding (TrB, group 13), 13 halogen bonding (HaB, group 17), 14 chalcogen bonding (ChB, group 16), 15 osme bonding (OmB, group 8), 16 spodium bonding (for group 12), 17 etc. Such names are proposed to differentiate these types of interactions from classical coordination bonds.…”
Section: ■ Introductionmentioning
confidence: 99%